SIMULATION OF AUTOMATIC TRAIN DOORSTOP USING HALL EFFECT A3144 SENSOR BASED ON ARDUINO UNO - Puguh Wiyono; Hartoyo Hartoyo (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
As a security for land traffic in the area of railroad crossing in general, a crossing is required. Increasingly busy traffic, the number of railroad crossings today, to prevent accidents either due to human error or the lack of compliance by motorists with traffic regulations, a controller that can regulate the flow of traffic at the railroad crossing is needed. The research objective was to design an automatic railroad crossing controlled by Arduino with the C language programming command. This research will make a prototype of the Automatic Crossing Gate using the halls effect A3144 sensor as an on and off switch by detecting the presence of a magnetic field (Lorentz force) on a passing train. The stages of the research method are: Provide the necessary components, namely Arduino, bread board circuit board, buzzer, A3144 sensor, LED, servo motor as a latch dynamo, Make programming tests on the Arduino for each buzzer, LED, A3144 sensor, servo motor as a latch dynamo, Assembling the overall components on the bread board as a model, Make overall programming on the Arduino from the circuit, and test the circuit on the bread model board,  Assemble the prototype clearly with a mini train accompanied by a rail with a loop in the form of a track, Test the maximum distance, the effective distance between the A3144 half effect sensor and the train.